PENGEMBANGAN PERTANIAN RENDAH EMISI SEBAGAI UPAYA PENGUATAN PROKLIM DI DESA WONOASRI KECAMATAN TEMPUREJO KABUPATEN JEMBER. - Ratnasari, Tri; Hari Setiyowati; Nilasari Dewi; Arif Mohammad Siddiq (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Abstract Climate change is a global phenomenon characterized by changes in patterns, intensity, or shifts in key climate parameters that impact ecosystems and human life. The effects of climate change are increasingly being felt, necessitating effective mitigation and adaptation efforts. The government has initiated the Climate Village Program (ProKlim) as an integrated strategy to reduce the impacts of climate change through local actions. Wonoasri Village, which directly borders the Meru Betiri National Park (TNMB), has implemented various environmental mitigation strategies, such as the development of alley forests and home gardens. However, mitigation efforts in the agricultural sector remain limited. The agricultural system applied in Wonoasri Village still largely relies on the use of chemical inputs, including fertilizers and pesticides, to support plant growth and resilience. The use of these chemicals has led to ecosystem degradation, as evidenced by the decline in populations of pollinating insects, birds, and other beneficial insects. Moreover, the excessive use of chemical fertilizers and pesticides has caused environmental damage, such as soil hardening and increased plant resistance to pests and diseases. In response to these issues, TNMB has collaborated with farmer groups through the Community-Based Forest Conservation Institution (LMDHK) to develop a low-emission agricultural system. Since 2017, initiatives have been implemented to reduce the use of chemical fertilizers by replacing them with solid organic fertilizers and liquid organic fertilizers (POC) derived from cattle and goat manure waste. This community service program aims to equip LMDHK members with the skills to process green waste into organic nutrient sources, particularly nitrogen (N), phosphorus (P), and potassium (K), which serve as organic fertilizers. Additionally, they are trained in producing botanical pesticides from green waste as an alternative to chemical pesticides for controlling plant pests and diseases. The primary goal of this initiative is to establish a low-emission agricultural system through the optimization of green waste utilization as a plant nutrient source and botanical pesticide. The implementation of this program is expected to help farmers reduce their dependence on chemical fertilizers and pesticides, thereby lowering agricultural production costs. Furthermore, this effort contributes to reducing greenhouse gas emissions through a sustainable agricultural system. The program is carried out through a series of activities, including program socialization, workshops on the production of organic NPK fertilizers and botanical pesticides, as well as monitoring and evaluation. The successful implementation of this program has resulted in organic fertilizer and botanical pesticide products that can be utilized by farmers as a concrete step towards achieving more environmentally friendly and sustainable agriculture. Keywords: ProKlim, Low-Emission Agriculture, Natural NPK, Botanical Pesticide